Theoretical investigation on the Cu(i)-catalyzed N-carboxamidation of indoles with isocyanates to form indole-1-carboxamides: effects of solvents. (3rd June 2020) - Yuan, Binfang; Wan, Jingwei; Guo, Xiaogang; Gong, Yongmi; Zhang, Fulan; Li, Qing; Wang, Guangzhao; Chen, Jinyang; He, Rongxing
Abstract : The solvents act as the hydrogen-bond acceptor to facilitate intermolecular addition, and then play the proton-shuttle to assist H1 + -shift. The stronger electron-donating property of solvent is favorable for the present Cu(i )-catalyzed reactions. Abstract : The mechanisms of Cu(i )-catalyzed N -carboxamidation of indoles with isocyanates are studied in detail to explore the effects of DMSO vs. THF vs. acetone based on theoretical calculations. The calculated results are shown as follows: (a) the Cu(i ) catalyst can activate the N1–C1 double bond of im1 to promote the intermolecular addition. (b) The solvents DMSO, THF and acetone can not only act as the hydrogen-bond acceptor to facilitate intermolecular addition between C1 and N2 by the hydrogen-bond N2–H1⋯O2 (O3 or O4), but also play the role of a proton-transfer shuttle in assisting the H1 + -shift by the stepwise proton-transport process (the protonation of solvent and the deprotonation of solvent-H + ). Due to the assistance of DMSO, THF and acetone, the rate-determining free energy barrier of the Cu(i )-catalyzed reaction is greatly reduced from 44.7 to 24.3, 25.6 and 28.6 kcal mol −1, which explains the experimental phenomena well (95% vs. 58% vs. 24% in yields). More importantly, the electron-donating ability of solvents (DMSO, THF and acetone) is found to be the primary factor that critically affects the catalytic activity of solvents, and the stronger electron-donating properties of solvents (DMSO > THF > acetone) are favorable for the present Cu(i )-catalyzed reactions. (c) Substrate 1a can also assist the reaction, but the catalytic capability of 1a is weaker than that of solvents DMSO, THF and acetone (energy barrier: 40.0 vs. 24.3, 25.6 and 28.6 kcal mol −1 ). Briefly, the present study is expected to help one understand the influence of solvents on the transition metal-catalyzed reactions including the addition reaction and the proton-transfer process.